Conceptualization of Campus Deradicalization and Development of Religious Moderation Paradigms in General Universities - Ahmad Yusuf Prasetiawan; Badrus Siroj; Musmuallim Musmuallim; Nur Rofiq (At-Tarbiyat, 2022)
This study aims to find out how Islamic religious education courses contain the concept of deradicalization in it and how far it has a role in developing the paradigm of religious moderation in higher education. Many studies mention the strength of radicalism in higher education, but Islamic religious education courses are not really a reference for students in religion. Students' religious understanding grows towards uncertainty because other sources such as religious study activities, books and the internet exceed the belief in Islamic religious education courses. The method in this research is a qualitative-descriptive survey research. Collecting data through in-depth interviews, field observations and documentation. The research locations were at three public public universities in Central Java, namely Semarang State University, Sebelas Maret University, Surakarta, and Jenderal Sudirman University. The results of the study indicate that PAI courses have not contributed much to the development of moderation da'wah and deradicalization efforts in higher education. Several factors that influence Islamic religious education courses cannot answer the problem of campus radicalism, namely in terms of learning strategies, lecturers, and the environment.